Perbandingan Emisi Karbon Dioksida Dari Penggunaan Lahan Permukiman Di Kawasan Urban Dan Peri-Urban Di Wilayah Gerbangkertosusila - Setiawan, Rulli Pratiwi (Jurnal Tata Kota dan Daerah, 2014)
This paper reviews the comparison of carbon dioxide emission from settlement land use between urban and peri-urban areas in the region of Gerbangkertosusila, in East Java. This paper is part of the research that addresses the comparison of greenhouse gas emission between urban and peri-urban areas of Gerbangkertosusila, which focused on settlement and agricultural land use. The region of Gerbangkertosusila itself consists of seven regencies/cities, namely Gresik, Bangkalan, Mojokerto, Sidoarjo, Lamongan, Surabaya and Mojokerto City. The first step is to classify the urban and peri-urban areas in Gerbangkertosusila. Classification of urban and peri-urban areas is determined through location quotient analysis as one of the economic base analysis techniques. The analysis shows that Surabaya City, Mojokerto City and Lamongan Regency are classified as urban, while Gresik, Bangkalan, Mojokerto and Lamongan are classified as peri-urban. The second step is to estimate the production of carbon dioxide emission from settlement land use in urban and peri-urban areas in Gerbangkertosusila. Carbon dioxide emission in urban areas is estimated at 8.35876E+14 TJ or accounts for 23% of emissions in the region Gerbangkertosusila, while carbon dioxide emissions in the peri-urban area is estimated at 2,8341E+15 TJ or approximately 77% of emission production in Gerbangkertosusila. The finding indicates that the contribution of settlements to the carbon dioxide emission in peri-urban area is very high in terms of the use of cooking fuel, whereas the land use of settlements as well as the number of household in peri-urban are much smaller than those in urban area. Keywords: carbon dioxide emissions, fuel consumption, land use, peri-urban, settlements, urban